1982
DOI: 10.2134/jeq1982.00472425001100030012x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Concentrations in Earthworms From Soil Amended with Sewage Sludge

Abstract: Metal concentrations in soil may be elevated considerably when metal‐laden sewage sludge is spread on land. Metals in earthworms (Lumbricidae) from agricultural fields amended with sewage sludge and from experimental plots were examined to determine if earthworms are important in transferring metals in soil to wildlife. Earthworms from four sites amended with sludge contained significantly (P < 0.05) more Cd (12 times), Cu (2.4 times), Zn (2.0 times), and Pb (1.2 times) than did earthworms from control site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(37 citation statements)
references
References 0 publications
3
34
0
Order By: Relevance
“…Chem. 18,1999 B.E. Sample et al (p ϭ 0.002), estimates did not differ significantly for Cd, Cu, Pb, or Zn (p Ͼ 0.05).…”
Section: Validation Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Chem. 18,1999 B.E. Sample et al (p ϭ 0.002), estimates did not differ significantly for Cd, Cu, Pb, or Zn (p Ͼ 0.05).…”
Section: Validation Resultsmentioning
confidence: 92%
“…Chem. 18,1999 B.E. Sample et al included pH more closely reflect the distribution of measured values than estimates generated by any other method.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ma (1982) investigated the influence of soil properties and wormrelated factors on the bioaccumulation of heavy metals in the earthworm Lumbricus rubel/us and found that the bioaccumulation factor almost never exceeded 1.0 and was negatively correlated with soil pH and CEC. Also investigating a Lumbricus species, Beyer et al (1982) observed that concentrations of Ni were less than or equal to the ambient concentration. In contrast to this, Gish and Christensen (1973) investigated soil and earthworm levels adjacent to three different roads.…”
Section: B Invertebratesmentioning
confidence: 99%
“…Earthworms have been widely studied as potential monitors of soil contaminant levels (Ash and Lee, 1980;Beyer et al, 1982;Gish and Christensen, 1973;Helmke et al, 1979).…”
Section: Biomonitor Speciesmentioning
confidence: 99%